A Review of Challenges and Developments in Wireless Channel Key Generation Technology - Zhang, Yu (Transactions on Computer Science and Intelligent Systems Research, 2024)
In recent years, physical layer security has become one of the core technologies for wireless communication system security. Physical layer encryption is based on the inherent reciprocity, time-varying, spatial uniqueness and unpredictability of wireless communication systems to generate keys, which are naturally unforgeable and steganography-proof. However, the research of physical layer key generation technology also faces many challenges, such as the problem of poor key generation performance due to signal interference, the problem of lower randomness and slower key generation rate in quasi-static channel environment, and the problem of lower key consistency between two legitimate communication parties due to the existence of channel estimation errors; this paper provides a systematic explanation of the traditional model of key generation for wireless channels and a typical solution for this series of problems. In this paper, the traditional model of wireless channel key generation is systematically explained, and the typical solutions to this series of problems are studied, analysed and compared in terms of performance.